Pengaruh Suasana Hati dan Kompetensi terhadap Kinerja Usaha melalui Kewirausahaan terhadap UMKM di Desa Tanjung Bumi Kab. Bangkalan - Moh. Abd. Rahman; Ahdiyat Agus Susila (Fakultas Ekonomi dan Bisnis Islam, 2021)
This study aims to determine the effect of mood on business performance, Testing the influence of individual moods on entrepreneurship, Testing the influence of competence on business performance, Testing the influence of competence on entrepreneurship, Testing the influence of individual moods on business performance through entrepreneurship, Testing the influence of competence on business performance. through entrepreneurship, Testing the influence of entrepreneurship on business performance. The results showed that, individual mood has no significant effect on business performance, mood has no significant effect on entrepreneurship, Competence has a significant effect on business performance, Competence has a significant effect on entrepreneurship, Competence has a significant effect on business performance through entrepreneurship, individual mood has no effect. significant towards business performance through entrepreneurship, entrepreneurship affects business performance.